“La Violencia Intrafamiliar en el marco de la Justicia Indígena” Trabajo de titulación previo a la obtención del título de magíster en Derecho Constitucional - Andrade Benavides, Paola Stefanía (2023)
The purpose of this project, entitled "Domestic violence in the framework of indigenous justice", is to identify the lack of protection of women's rights in the area of indigenous prosecution of cases of domestic violence to the authority of the community; as well as to know about indigenous justice and its forms of application. Additionally, to recognize it in the international and national legal framework to carry out the analysis of the information in a critical and juridical manner. For the development of this study, a mixed approach methodology was used, that is, the qualitative and quantitative aspects were applied to achieve the result that allows responding to the problems of the research, referring to the fact that the naturalization of domestic violence in indigenous communities favors leaving these crimes unpunished; that is why, as a research tool, surveys were applied to indigenous women, which resulted in a feeling of impunity for women, at the time of a complaint of this type of facts to the indigenous authorities.